MENUMBUHKAN DAN MENGEMBANGKANETIKA, MORALITAS DAN SPIRITUALITAS DALAM PENEGAKAN HUKUM PAJAK - Wahyudi Wahyudi (INTELIGENSIA MEDIA, 2023)
Justice as the essence of law is a basic spiritual need of society. Without the availability of rational and good law, a society will be sick. Law cannot be separated from the spiritual structure of society, because law is essentially a part of culture, an incarnation of the personality of society and correlates with the structure of thinking and the value base of society. In this case the law determines an act that may or may not be performed. The essence of a good law will always respond and rectify the imbalance in the implementation of obligations compared to the rights of every citizen or community group as supporters of the law. At the pre-conventional level, motivation for moral decisions comes from fear of punishment (stage 1) or from self-interest, such as meeting one's own needs (stage 2). At the conventional level, the influence of moral decisions comes from social groups so that individuals act to please or help others (stage 3) or to comply with social, legal or religious norms; also called rule-based moral reasoning (stage 4). Finally, at the postconventional level, individuals make ethical decisions based on concepts of justice such as individual rights and socially accepted standards (stage 5) or universal ethical principles as defined by the individual's conscience (stage 6).